Hubungan Antara Dukungan Sosial dengan Tingkat Kecemasan pada Pasien Kanker Payudara - Nurhidayah, Dwi; Mulidah, Siti; Purnomo, S.Eko Ch.; Sudiarto, Sudiarto (Prodi Keperawatan Purwokerto, 2024)
Background: Breast cancer is the most common cancer experienced by women. In Indonesia, there are 68,858 cases of breast cancer with 30.9% of them in Central Java. The impact on the bio-psychosocio-spiritual aspects of breast cancer patients is anxiety. One effort to reduce anxiety levels in patients is to provide social support. Objective: To determine the relationship between social support and the anxiety level of breast cancer patients. Methods: The research design used is descriptive quantitative with correlational methods and cross-sectional approaches. A total of 60 respondents were selected using the consecutive sampling technique. The Medical Outcomes Study Questionnaire: Social Support Survey (MOS: SSS) was used to measure social support and the State-Trait Anxiety Inventory (STAI) to measure anxiety levels. Data analysis used Spearman's rank test. Results: There are 54 respondents of 60 respondents who have received social support in the high category, while the level of anxiety they experience tends to be in the low category (65.3%). The results of Spearman's Rank analysis showed a social relationship with anxiety (p-value = 0.021, rcount = 0.298) which means that the higher social support received, the lower the level of anxiety experienced by breast cancer patients. Conclusion: There is a negative correlation between social support and anxiety levels in breast cancer patients. The higher the social support the patient gets, the lower the level of anxiety in breast cancer patients.Â